Commuting and the Motherhood Wage Gap: Evidence from Germany - Thomas Skora (Sustainability, 2020)
In the present study, we analyze how childbirth-related changes in commuting contribute to the motherhood wage gap, which in turn accounts for a large part of the gender pay gap. Derived from human capital theory and job search theory, we examine various mechanisms that might explain why reduced commuting distances after childbirth come along with wage reductions for mothers. The empirical analyses are based on data from the German Socio-Economic Panel (GSOEP) 2001–2017, which are analyzed within a fixed effects (FE) panel framework (n = 41,111 observations from 7183 persons). Firstly, the results show that the transition to first parenthood is associated with a 33% decrease in the commuting distance of women, while the transition to fatherhood has no effect. Secondly, mothers who substantially reduce their commuting distance after the transition to parenthood (who amount to 30% of all mothers in our sample) show an increased wage penalty (−18.4%), compared to mothers who do not reduce their commuting distance (−8.7%). Accordingly, 23% of the motherhood wage penalty can be attributed to wage losses related to the reduction in commuting distance. Thirdly, wage penalties for mothers who change to a job closer to their place of residence can be partly explained by the loss of firm-specific human capital. In addition, the wage penalty for commuting is a consequence of women taking jobs that are less suited to their skills profile and moving to smaller companies.